Systems Thinking and Business Resilience: Questions That Should Keep Us Up at Night. Issue 2 (6th August 2021) - Siviy, Jeannine; Kim, Gene
ABSTRACT: As interdisciplinary systems thinkers, we in the systems engineering field – especially the members of the Systems and Software Interface Working Group (SaSIWG) – are wired to believe that a "systems mindset should be everywhere." To catalyze the conversation about increasing the relevance of systems engineering and systems thinking in software‐ and data‐intensive settings, this paper offers eight thought questions, which span governance, people, process, technology, and business concerns. The goal: resilience in the face of ever‐increasing volatility and complexity. Join our conversation!